Pemikiran Pendidikan Islam Ahmad Dahlan - Desi Ratna Sari; Novita Sari; Dwi Noviani; Paizaluddin Paizaluddin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Ahmad Dahlan was born in Jogyakarta in 1868 AD/ 1268 AH, the figure of K.H. Ahmad Dahlan, who is known as a figure in the Islamic reformist and reformist movement, bravely and seriously put education as a strategic means and effort to save Muslims from static thinking, because at that time Indonesian society experienced colonialism from Dutch and Japanese colonialists. towards dynamic thinking to realize Indonesian independence. The spirit of struggle initiated and carried out by K.H. Ahmad Dahlan implemented this by establishing educational institutions which were then used as cadre formation centers for Indonesian Muslims. K.H. Ahmad Dahlan believes that education is capable of turning humans into perfect humans. In general, Ahmad Dahlan's reform ideas can be classified into two dimensions, namely: first, trying to purify Islamic teachings from khufarat, superstition and heresy which have been mixed into the beliefs and worship of Muslims. Second, inviting Muslims to leave the network of traditional thought through re-interpretation of Islamic doctrine in formulations and explanations that can be accepted by reason.